Effects of Language Proficiency on Selective Attention Patterns at Segmenting Boundaries in English Audio Sentences - Yunhao Mei; Fei Chen; Xiaoxiang Chen (Brain Sciences)
Background/Objectives: Normative perceptual segmentation facilitates event perception, comprehension, and memory. Given that native English listeners’ normative perceptual segmentation of English speech streams coexists with a highly selective attention pattern at segmentation boundaries, it is significant to test whether Chinese learners of English have a different attention pattern at boundaries, thereby checking whether they perform a normative segmentation. Methods: Thirty Chinese learners of English with relatively higher language proficiency (CLH) and 26 with relatively lower language proficiency (CLL) listened to a series of English audio sentences. Meanwhile, they were asked to press the key whenever a phonetic probe “ba” occurred. Response time to “ba” reflects the attention where “ba” is located at segmentation boundaries. Results: The results revealed that, (1) relative to native English listeners’ highly selective attention pattern, the CLH group showed a relatively selective attention pattern, while the CLL group displayed a non-selective attention pattern. (2) Both the CLH group and natives had better recognition memory than the CLL group. (3) Both the CLH group and natives’ attention at segmentation boundaries was not correlated with their memory for sentences, while the CLL group’s attention at boundaries was correlated with memory. Conclusions: These findings suggest that (1) Chinese learners of English did not perform a normative segmentation, which shows the effect of English proficiency on perceptual segmentation; (2) English proficiency has a superior effect on memory for sentences, while perceptual segmentation would come next to support memory by providing structure for memory construction if English proficiency is not high; (3) a comparison of attention patterns between Chinese learners and natives can provide a reference for potential intervention to rectify non-natives, thereby improving their perception of English speech streams.